Pengaruh gelombang mikro pada pembuatan biodiesel dan kualitas metil ester dari minyak goreng kelapa sawit dan minyak goreng kedelai menggunakan katalis naoh terhadap kualitas metil ester - Faradillah, Husnah; Suryanto, Andi; Rasyid, Rismawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The use of microwaves in the biodiesel production process has been widely used because it has many advantages, one of which is showing a more efficient reaction, with a short reaction time and separation process. It is necessary to determine the effect of microwaves on the quality of biodiesel from palm oil and soybean oil. The aim of the research was to: 1) Evaluate the effect of power on the yield of palm oil and soybean oil biodiesel with a mole ratio of 1:12, reaction time of 2.5 minutes, and NaOH catalyst concentration of 0.2%. 2) Evaluate the effect of power on the characteristics of palm oil and soybean oil biodiesel with a mole ratio of 1:12, reaction time of 2.5 minutes, and NaOH catalyst concentration of 0.2%. 3) Evaluate the effect of power on the quality of palm oil and soybean oil biodiesel methyl ester compounds with a mole ratio of 1:12, reaction time of 2.5 minutes, and NaOH catalyst concentration of 0.2%. This research was carried out by preparing samples of oil, methanol, catalyst and distilled water. Followed by weighing the 0.2% catalyst and dissolving it with methanol and oil with a mole ratio of 1:12 then reacting with a microwave method transesterification reaction with power variations of 100, 264, 400 watts and a reaction time of 2.5 minutes. The results of transesterification produce biodiesel and glycerol. Biodiesel is separated for the purification process. The results of biodiesel purification are followed by physical and chemical testing. The results of this research show that: (1) The yield of palm oil biodiesel was 96% with a power of 400 watts and the yield of soybean oil biodiesel was 92% with a power of 400 watts. (2) The characteristics show that they are in accordance with SNI 7812:2015, except for water content. (3) The optimal % area of methyl ester obtained from palm oil biodiesel is 55.23% of 400 watt power and 37.38% of 264 watt power from soybean oil biodiesel.